The household as a source of labor for entrepreneurs: Evidence from New York City during industrialization. (27th December 2018) - Ruef, Martin
Abstract : Research Summary: This article conceptualizes households as a crucial pool of labor for small entrepreneurs. The household varied historically in its scope (depending on whether bonded workers were included) and work intensity (depending on the authority or coercion exercised by household heads). Drawing on data that enumerate over 100, 000 households in New York City, I examine how the shift from institutions of unfree labor to wage labor affected business proprietorship between 1790 and 1850. Given the disproportionate importance of unfree household labor to small entrepreneurs, the contraction of this labor source may offer one general explanation for their decline. Managerial Summary: How does household scope and composition affect the ability of an individual to run their own business? Historical archives can provide useful insights into this question. They track long‐term declines in family size and the emancipation of non‐family members—such as apprentices, indentured servants, and slaves—from the authority of household heads. Examining records from early New York City, this study shows that business ownership was strongly linked with the ownership of slaves and the presence of dependent males after the American Revolution. Large households and unfree laborers were especially important for entrepreneurship among individuals with limited wealth. For modern economies, the results suggest that policymakers consider potential tensions between small business ownership and the development of free and equitable labor markets.